Harry Potter: campo literário e mercado, livros e matrizes culturais - Borelli, Silvia Helena Simões (2006)
This is an essay about Harry Potter, the series of books of the British writer Joanne Kathleen Rowling, published originally by the Bloomsbury Publishing Plc, since 1997, translated to countless idioms and divulged and consumed, world-widely, by the market strategies of symbolic goods, the books arrived in Brazil in the year 2000, edited by Rocco. The aims of this refl ection are: 1) to understand the book in a di men sion of exteriority, which includes a more general system of cultural pro duc tion in the contemporaneousness; to face it, as a strategic object inside the literary fi eld and the symbolic goods market; 2) to conceive the book in your dimension of interiority and consider it from its singular narrative in which it is support and porter: what stories are these; which cultural ma trix es they belong; which fi ctional territories they dialog; how they become capable of reproducing a time spirit and capable of producing new imag i nary orders; 3) to scan the book following its trajectory of literary fi eld mi gra tion towards other cultural forms: from the transformation of the writ ten words in cinematographic or digitized images